Ergonomic Method to Reduce the Risk Level of Musculoskeletal Disorders in a Garment Manufacturing SME in Lima, Peru - Ortiz Porras, Jorge (2023)
In Peru, the textile industry represents a very important sector due to its significant contribution to the national GDP. All 398 thousand workers in this sector are prone to suffer from musculoskeletal disorders (MSDs), since the operation of machinery and handling of materials involves prolonged repetitive movements, causing strain on the body. This research aims to reduce the risk level of MSDs in a garment manufacturing SME. Therefore, an ergonomic method was developed based on REBA and RULA integration, which also proposes preventive and corrective measures. A initial evaluation was performed based on the observed postures of the operators to identify the risk levels; subsequently, the evaluation was repeated upon the implementation of the method in order to estimate its effectiveness. As a result, there was an improvement of 44.97%, that is, the level of risk to which the workers are exposed was reduced, demonstrating that the method is useful for garment manufacturing SMEs.